Genome-wide identification, evolution and transcriptome analysis of GRAS gene family in Chinese chestnut (Castanea mollissima) - Yu, Liyang; Hui, Cai; Huang, Ruimin; Wang, Dongsheng; Fei, Cao; Guo, Chunlei; Zhang, Jingzheng (Frontiers in Genetics, 2023)
Abstract GRAS transcription factors play an important role in regulating various biological processes in plant growth and development. However, their characterization and potential function are still vague in Chinese chestnut (Castanea mollissima), an important nut with rich nutrition and high economic value. In this study, 48 CmGRAS genes were identified in Chinese chestnut genome and phylogenetic analysis divided CmGRAS genes into nine subfamilies, and each of them has distinct conserved structure domain and features. Genomic organization revealed that CmGRAS tend to have a representative GRAS domain and fewer introns. Tandem duplication had the greatest contribution for the CmGRAS expansion based on the comparative genome analysis, and CmGRAS genes experienced strong purifying selection pressure based on the Ka/Ks. Gene expression analysis revealed some CmGRAS members with potential functions in bud development and ovule fertility. CmGRAS genes with more homologous relationships with reference species had more cis-acting elements and higher expression levels. Notably, the lack of DELLA domain in members of the DELLA subfamily may cause de functionalization, and the differences between the three-dimensional structures of them were exhibited. This comprehensive study provides theoretical and practical basis for future research on the evolution and function of GRAS gene family.